How Product Development Accelerating Approaches Influence Product Development Performance - An Empirical Study in Turkish Automotive Sub-Industry - (:unkn) unknown (My University, 2010)
In this study, the accelerating approaches of product development (PD) process that are classified as five factors (Simplification of PD Operations, Elimination of Delays in PD Process, Acceleration of PD Operations, Concurrent Engineering, Involvement of Lead Users in PD Process, Supplier Involvement in PD Process) influencing PD performance at automotive sub-industry firms is investigated. A detailed questionnaire is conducted aiming to unveil the impact of the independent variables in our original theoretical model on the product development performance in the automotive sub-industry. The questionnaire aiming to obtain the relevant data is carried out on 51 medium and large scale companies performing in Gebze, Istanbul - Turkey. The data obtained are evaluated by using the SPSS 10.0 statistical analysis program. The frequency tables related with the data on participant companies, the factor analysis results with the variables in the theoretical model, the reliability analysis results, correlation analysis, the average and standard deviation and regression analysis were stated. The approaches to accelerating the product development process, namely simplifying the product development operations, accelerating the product development operation, the use of concurrent engineering approach, the involvement of main suppliers and lead users in product development process, have effected meaningfully and positively the product development performance. The conclusions drawn from our findings were discussed in detail and compared with the previous works. According to findings of the study, Turkish automotive sub-industry firms should decrease PD cycle times by accelerating PD operations, involving lead users and suppliers in PD process, using concurrent engineering approach in PD and simplifying PD operations. Thus, they can accelerate their PD processes and increase their PD performance. The results of this study and its theoretical model provide valuable insight into managing of the PD process in automotive sub-industrial firms, other practices relating this topic and academicians who will study on this topic.
Keywords: Product development accelerating methods; Product development performance; Regression analysis